The SON2A2 score: A novel grading scale for predicting hemorrhage and outcomes after thrombolysis - Ren, Yu; He, Zhongxiang; Du, Xiaoyan; Liu, Jie; Zhou, Li; Bai, Xue; Chen, Yue; Wu, Bowen; Song, Xiaosong; Zhao, Libo; Yang, Qin (Frontiers in Neurology, 2022)
Abstract Objectives: This study aimed to develop a score including novel putative predictors for predicting the risk of sICH and outcomes after thrombolytic therapy with intravenous (IV) recombinant tissue-plasminogen activator (r-tPA) in acute ischemic stroke patients. Methods: All patients with acute ischemic stroke treated with IV r-tPA at 3 university-based hospitals in Chongqing, China, from 2014 to 2019 were retrospectively studied. Potential risk factors associated with sICH (NINDS criteria) were determined with multivariate logistic regression and we developed our score according to the magnitude of logistic regression coefficients. The score was validated in another independent cohort. Area under the receiver operating characteristic curve (AUC-ROC) was used to assess the performance of the score. Calibration was evaluated using the Hosmer-Lemeshow goodness-of-fit method. Results: The SON2A2 score (0 to 8 points) is consisted of history of Smoking (no=1, yes=0, β=0.81), Onset-to-needle time (≥3.5=1,<3.5=0, β =0.74), NIH Stroke Scale on admission（>10 =2, ≤10=0, β=1.22）, Neutrophil percentage（≥80.0%=1,<80%=0, β=0.81）, ASPECT score (≤11= 2, >11=0, β=1.30) and Age (>65 years =1, ≤65 years =0, β=0.89). The SON2A2 was strongly associated with sICH (OR 1.98; 95%CI, 1.67-2.34) and poor outcomes (OR 1.89; 95%CI, 1.68-2.13). AUC-ROC in the derivation cohort was 0.82 (95%CI, 0.77-0.86). Similar results were obtained in the validation cohort. The Hosmer–Lemeshow test revealed that predicted and observed event rate in derivation and validation cohorts were very close. Conclusions: The SON2A2 score is a simple, efficient, quick, and easy-to-perform scale for predicting the risk of sICH and outcome after intravenous r-tPA thrombolysis within 4.5 hours in patients with ischemic stroke, risk assessment using this test has the potential for early and personalized management of this disease in high-risk patients.